Impact of COVID-19 on Dry fish Production and Marketing from India - V. Geethalakshmi; V. Chandrasekar; Nikita Gopal (Fishery Technology, 2022)
Drying is one of the oldest known techniques for preservation of fishes. Dry fish is a commodity which has demand both within and outside India. Indian dry fish exports contribute 7.45% to the total marine product exports valued at USD 156.94 million during 2020-21. The COVID-19 imposed lockdown led to disruptions in several segments of the economy and dry fish sector was no exception. The dry fish production is carried out as a smallscale activity along the coastal belt of the country providing source of livelihood for thousands of fisherfolk especially women. The dry fish value chain involves many players starting from fresh fish supplier, dry fish processor, dry fish agent, wholesaler, retailers and consumers. Owing to the outbreak of COVID-19 and the subsequent lockdown enforced from 24th March 2020, small scale dry fish processors suffered losses which have been estimated to the tune of Rs.0.5 to 1 lakh per month depending on the capacity of the unit. Women involved in household drying of fish experienced losses amounting to Rs.10,000 to Rs.12,000 per month. The dry fish exports from India, although seasonal has also registered a decline during the first three months of the pandemic and ensuing lockdown period. This paper presents an assessment of the impacts on the dry fish sector in the country.